(untitled) (Research, Society and Development, 2021)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae. The treatment of leprosy is the multidrug therapy – MDT, an association of Rifampicin, Dapsone, and Clofazimine that can cause several adverse events. This paper aims to analyze the scientific productions about aspects related to side effects, adverse reactions, and/or signs and symptoms concerning medications in the use of combination and/or alternative chemotherapy used to treat leprosy. This is an integrative review for which the PubMed, LILACS, CINAHL, and Google Scholar databases were selected to search for primary studies, published between 1991 and 2020, in Portuguese, English, and Spanish. A total of 4.724 studies were identified, with 50 eligible papers, of which 33 comprised the final sample. The main themes presented by the papers were: MDT available to treat leprosy and its complications; implications and adverse effects caused by medications; actions to mitigate these effects; training for the health personnel on the treatment effects; relevance of warning the patient about the treatment and its adverse effects; the importance of quickly diagnosing and treating DHS; monitoring of laboratory tests; preventive measures to treat potential complications; notification of adverse effects and scarcity of multicentric studies that assess adverse effects and efficacy of treatment. The permanent training and education of the management and multidisciplinary health teams are necessary so that the actions have a positive impact on the quality of care provided, thus benefiting the implementation of mechanisms for surveillance and control of adverse reactions.